Penilaian Kebijakan Publik Atas Pelayanan Pajak Kendaraan Bermotor di Sistem Administrator Manunggal Satu Atap - khamim, mukhamad; Indriasari, Evy (Universitas Pancasakti Tegal, 2021)
This research is a conceptual study to assess the quality of public services. Public Service is a public service carried out by the organizer to improve the quality and guarantee the provision of public services in accordance with the general principles of good government and corporations and to provide protection for every citizen and resident from abuse of authority in the provider of public services, legal arrangements are needed that support it. Public services about motor vehicle taxpayers in the SAMSAT office of Brebes Regency we can take care of it ourselves without being represented by others. Supporting factors and inhibiting factors for Motor Vehicle Taxpayer Services have used an Online system that makes it easier for the public to Extend Motor Vehicle Taxpayers, the environment around the SAMSAT Brebes Office is comfortable and safe which makes people feel comfortable when they are doing motor vehicle taxpayers It is necessary to improve excellent service to the community regarding services for the obligation to pay vehicle taxes and implement the SAMSAT program traveling regularly in places far from reach or in remote rural areas this embodies a commitment to providing the best service for the community.